Cultura financiera y la toma de decisiones en trabajadores de empresas ferreteras de la ciudad de Iquitos, periodo 2022 - Da Silva Villacorta, Karola (2023)
Financial culture is related not only to the set of knowledge in financial matters that people possess, but also to education and values regarding the proper management of their personal finances, in such a way that it generates in them the necessary awareness to make decisions. correct and coherent statements on the proper use of the financial resources they have or manage in their daily activities. The research is entitled "Financial Culture and Decision Making in workers of hardware companies in the city of Iquitos, period 2022", with the main objective of determining the relationship between financial culture and decision making. The research had a quantitative approach and a descriptive correlational design, using the survey technique and the data collection instrument, the questionnaire of resolved questions, the latter being subjected to an evaluation by experts who agreed to be used in a population comprised of only 31 operational workers from the different hardware companies in the city. Finally, the information was analyzed by means of the spss v25 statistical software, determining that there is a strong and directly proportional positive relationship, supporting through Spearman's Rho coefficient that it was 0.803 and a degree of significance of 0.000.